(untitled) (Kronika Bydgoska, 2020)
References to Europe can be made on several different grounds. Europeanness of Bydgoszcz during the 1920s meant primarily interest in the policy as well as social and cultural issues of Europe. The editors of the daily “Dziennik Bydgoski” informed in detail about important European events, which could be of interest to the residents of Bydgoszcz. These issues could have an impact on the terms of the Treaty of Versailles as well as international relations in general. However, Europeanness of Bydgoszcz did not obscure the Polish egocentrism of its residents, where the national matters seemed to have priority.